The Importance of Civic Education for Building Student Character in Elementary Schools - Nasution, Zahira Andryani (International Journal of Students Education, 2024)
This paper aims to find out and explain the role of civic education in forming character in elementary school students. The research method uses literature review or literature review sourced from books, relevant journals that have existed before, and scientific articles. This study explains the role of civic education (PKN) subjects in elementary schools in character formation efforts. The results of the study indicate that civic education has an important role in character formation for the nation and state to become better individuals. Civic education in its teaching has a major impact on the development of the character of elementary school students. In civic education, students can learn to become humans with good character and be responsible as citizens. This civic education must continue to exist in order to create and foster young generations with character in the life of the nation and state for the progress of the nation and the next generation.